Admissible and locally admissible varieties of algebras - Roldan Urrutia, Ronald Alexandre (2024)
The question of admissibility was afirmatively solved for Jordan and Alternative algebras and Octonions, logically the question was extended for Sedenions and here we present some advances in such problem. In 1993 Schafer classified finite dimensional central simple non-commutative Jordan algebras encountering four possibilities: Central Simple Jordan algebra Central Simple associative algebra Octionion algebra Color algebra Consequently was arised a new question about determining the admissibility of the last algebra of the classification and here it is expoused some results concerning to it.